Preload-adjusted maximal power: a novel index of left ventricular contractility in atrial fibrillation. Issue 2 (1st August 2002) - Takagaki, M; McCarthy, P M; Chung, M; Connor, J; Dessoffy, R; Ochiai, Y; Howard, M; Doi, K; Kopcak, M; Mazgalev, T N; Fukamachi, K
Abstract : Background: Left ventricular contractility in atrial fibrillation is known to change in a beat to beat fashion, but there is no gold standard for contractility indices in atrial fibrillation, especially those measured non-invasively. Objective: To determine whether the non-invasive index of contractility "preload-adjusted PWRmax " (maximal ventricular power divided by the square of end diastolic volume) can accurately measure left ventricular contractility in a beat to beat fashion in atrial fibrillation. Methods: Atrial fibrillation was induced experimentally using 60 Hz stimulation of the atrium and maintained in 12 sheep; four received diltiazem, four digoxin, and four no drugs (control). Aortic flow, left ventricular volume, and left ventricular pressure were monitored simultaneously. Preload-adjusted PWRmax, the slope of the end systolic pressure–volume relation (Emax ), and the maximum rate of change of left ventricular pressure (dP/dtmax ) were calculated in a beat to beat fashion. Results: Preload-adjusted PWRmax correlated linearly with load independent Emax (p < 0.0001) and curvilinearly with load dependent dP/dtmax (p < 0.0001), which suggested the load independence of preload-adjusted PWRmax . After five minutes of diltiazem administration, preload-adjusted PWRmax, dP/dtmax, and Emax fell significantly (p < 0.0001) to 62%, 64%, and 61% of baseline, respectively. Changes were not significant after five minutes of digoxin (103%, 98%, and 102%) or in controls (97%, 96%, and 95%). Conclusions: Preload-adjusted PWRmax correlates linearly with Emax and is a useful measure of contractility even in atrial fibrillation. Non-invasive application of this method, in combination with echocardiography and tonometry, may yield important information for optimising the treatment of patients with atrial fibrillation.